2017 Roger A. Mann Award Winner: Correlation of Hallux Rigidus Coughlin Grade with First MTP Motion, Intra-operative Cartilage Loss and Treatment Success for 1st MTP Arthrodesis and Hemi-Arthroplasty. Issue 3 (11th September 2017) - Baumhauer, Judith F.; Singh, Dishan; Glazebrook, Mark; Blundell, Chris; de Vries, Gwyneth; Le, Ian L.D.; Nielsen, Dominic; Pedersen, M. Elizabeth; Sakellariou, Anthony; Solan, Matthew; Wansbrough, Guy; Younger, Alastair S.E.; et al.
Category: Midfoot/Forefoot Introduction/Purpose: Hallux rigidus (HR) is a very common symptomatic problem affecting one in 40 patients over the age of 50 years. A variety of treatment options exist and, as is common in surgery, grading systems are used to assess severity of the condition and aid in the guidance of treatment. The most commonly used grading system for HR uses radiographic images, great toe range of motion and clinical symptoms. This study examines the relationship of radiographic and motion findings to observed intra-operative cartilage loss in patients with HR and explores hallux rigidus grade and cartilage loss as predictive variables for treatment outcomes. Methods: A prospective, randomized non-inferiority study examining outcomes of arthrodesis compared to hemiarthroplasty of the first metatarsal phalangeal joint (Cartiva®) was performed.2 All randomized and treated patients were included in this study. Patients underwent pre-operative clinical examination, including measures of joint motion, radiographic assessment and HR grade. Operatively, observations of cartilage loss on the metatarsal head and opposing proximal surfaces were recorded. All patients' data, irrespective of treatment, were aggregated and Spearman Rank Correlation coefficients used to assess for strength of correlation of active peak dorsiflexion and cartilage loss to HR grade. Outcomes data were then separated by treatment group and two-sided Fisher's Exact test assessed these variables' impact on clinical success (p<0.05). Results: In 202 patients, 59 (29%), 110 (55%), and 33 (16%) were classified as Coughlin1 Grades 2, 3, and 4, respectively. There was no correlation between grade and active peak dorsiflexion (-0.02, p=0.78). While rank correlations between grade and cartilage loss on the proximal phalanx and metatarsal head statistically significantly differed from zero, the magnitudes of the correlations were small, 0.176 (p=0.01) and 0.224 (p=0.001), respectively (Table 1). Among Grade 4 patients, 36.4% had no metatarsal cartilage remaining; but this was also found in 8.5% of Grade 2 patients. Similarly, 52.5% of Grade 2 patients had ≥50% metatarsal cartilage remaining; but this was also found in 21.2% of Grade 4 patients. None of the observed factors were significantly associated with likelihood of achieving composite success. Conclusion: This study examines the relationship of motion and intra-operative cartilage loss findings with a commonly used clinical and radiographic grading system for hallux rigidus. This study population included only candidates with HR considered a candidate for arthrodesis based on review of clinical symptoms however the Grade assigned maybe Coughlin Grade 2, 3 or 4. Irrespective of the Grade, positive outcomes were demonstrated within both treatment groups. The weak correlations of preoperative motion and intra-operative cartilage loss to grade suggests that clinical symptoms should be a significant determinant guiding the treatment option rather than radiographic or range of motion factors.